Experimental study on cyclic behavior of cast steel connectors for beam-to-column joints. Issue 11 (November 2016) - Chen, Yingzhi; Tong, Lewei; Chen, Yiyi; Zhou, Xin
This article presents an experimental study on two innovative types of cast steel connectors, which would be used as a replaceable energy-dissipating component in the beam-to-column joint. The main aim was to use the connectors as the main source of deformation and energy dissipation, and to realize rapid repair of the joints by simple replacement of these connectors after earthquakes. A total of eight cyclic tests under two loading procedures were conducted on three types of connectors, namely, traditional welded T-stubs W, C1 type cast steel connectors, and C2 type cast steel connectors. The new cast steel connector specimens were observed to have good energy dissipation capacity with stable and plump hysteretic curves, and the equivalent viscous damping could achieve up to 43.7%. The ductility, which was governed by fracture of energy-dissipating elements, was shown to be satisfactory. The L / t ratio (the length of energy-dissipating element to its thickness ratio) was found to be an important factor influencing the cyclic performances of C2 connectors. The accumulated plastic damage of C2 connector caused by bidirectional reversed tension and compression actions did not significantly weaken its energy dissipation capacity, which demonstrated the feasibility of employing C2 connector only in the beam bottom flange of a beam-to-column joint.